(untitled) (Journal of Veterinary Medicine and Animal Production, 2022)
The incidence of infectious bursal disease (IBD) among cases submitted to the poultry diseases and diagnosis Department, (VRI) Khartoum-Sudan was investigated during the years 2000-2012. The overall incidence of IBD cases was 4.2%. The highest rate (12%) was reported in the year 2000 and the lowest (2%) in 2009. The outbreaks were more recorded in Summer (No.=55) than in Autumn (No.=26) and Winter (No.=19) seasons. From the total IBD outbreaks, 62% occurred in layer chickens and 32 % in broiler chickens. Among chicken breeds affected, the Hisex represented (25%) followed by Bovans (22%) and least the Hypro breed (3%). It was noted that highest IBD cases (38.3%) were reported in 16-30 days old chickens, 36.2% in the age group 31-45 days and the least (2.1%) in the age group 0-15 days old. It was concluded that IBD continues to be a serious problem to the poultry industry in Sudan. Comprehensive studies are needed to isolate and characterize the field viruses and study the effectiveness of vaccines used.